Analisis Beban Kerja: Instrumen Penting untuk Mewujudkan Organisasi Birokrasi Yang Efektif (Analisa Kasus pada Kegiatan Kajian/Penelitian di Lingkungan PKP2A I LAN) - Rejeki, Putri Wulandari Atur (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
Indonesian bureucracy that acts as reflection on public organization wheter in central or province level is suppose to be supported by resources. One of the resources that have strategic value and important role in enforcing organization is human resources. Workload dimension is an interesting matter to discuss. The article tries to elaborate on research unit in PKP2A I LAN